Relationship of PPARG overexpression with prognostic parameters in papillary thyroid carcinoma - ASYA, ORHAN; YUMUŞAKHUYLU, ALİ CEMAL; BAĞCI ÇULÇİ, PELİN; ŞAHİN, AKIN; OYSU, ÇAĞATAY; KAYA, HANDAN (My University, 2022)
Objectives. PAX8/PPARG chromosomal rearrangement is frequently seen in thyroid cancer, and PPARG overexpression has been shown in the follicular variant of papillary thyroid carcinoma, but not in papillary thyroid carcinoma other than the follicular variant. The main aim of this study was to investigate the frequency of PPARG overexpression among papillary thyroid carcinoma and if there were any variants of papillary thyroid carcinoma with PPARG overexpression other than the follicular variant. Methods. Immunohistochemical analysis of PPARG overexpression was performed using a PPARG monoclonal antibody in a series of 111 paraffin-embedded blocks of thyroid tumours. Of the patients in our study, 100 were diagnosed with papillary thyroid carcinoma, 9 with follicular adenoma and 2 with follicular carcinoma. Results. PPARG staining was detected in 19 of the 111 cases. Sixteen patients with PPARG overexpression had papillary thyroid carcinoma and 3 had follicular adenoma. Conclusion. PPARG overexpression was detected mainly in follicular-variant papillary thyroid carcinoma. Vascular invasion, lymphatic invasion, thyroid capsule invasion and lymph node positivity were lower in patients with PPARG overexpression.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Medicine; Health Sciences; Surgery Medicine Sciences; Otolaryngology; KULAK BURUN BOĞAZ; Klinik Tıp; Klinik Tıp (MED); OTORHINOLARYNGOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Otorhinolaryngology; Speech and Hearing; papillary thyroid carcinoma; PPARG overexpression; prognostic parameters; FOLLICULAR VARIANT; FUSION PROTEIN; CANCER; THERAPY; CONTROVERSIES; MANAGEMENT; EXPRESSION; papillary thyroid carcinoma; PPARG overexpression; prognostic parameters; PAX8/PPARG fusion protein (PPFP); pioglitazone